Penilaian Standar Pariwisata Berbasis Komunitas (CBT) dalam Pengembangan Wisata Puncak Pagerbatu, Kota Banjar - Prayoga, Firman; Wahyono, Hadi (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2024)
The tourism sector is one of the sectors that has a major contribution to the growth of a country that contributes to creating new jobs and increasing foreign exchange. The focus of tourism development today lies in sustainable tourism development initiatives, which seek to achieve a balance between industrial, social, and economic activities. CBT (Community Based Tourism) is a form of tourism that empowers communities to organize and manage tourism growth and benefit in terms of economic, social, and sustainable environmental development. This research aims to assess the sustainability of Pagerbatu Peak Tourism, Banjar City based on indicators in the ASEAN Community Based Tourism (CBT) Standard. The method used is qualitative descriptive by utilizing field observations and interviews in extracting information and data. The results show that most of the criteria still cannot be fulfilled comprehensively. The lack of fulfillment of CBT standards on Pagerbatu Peak Tourism is partly due to the operationalization period of tourism which is not so mature so that synergy between many parties is needed in the process of developing Pagerbatu Peak Tourism, Banjar City.